Mechanical design and control of inflatable robotic arms for high positioning accuracy. (17th January 2018) - Kim, Hye-Jong; Kawamura, Akihiro; Nishioka, Yasutaka; Kawamura, Sadao
Abstract: In recent years, inflatable robotic arms have been developed so that physical contact with humans and working environments could be performed safety. In industry, there is a growing demand for safe industrial robots to collaborate with people and work in various environments. In general, however, the positioning accuracy of inflatable robotic arms has not been discussed. This paper proposes an inflatable link structure and a non-inflatable joint structure that could realize a high positioning accuracy for such robotic arms. This paper experimentally demonstrates that these structures can improve positioning accuracy. In addition to these structures, the joint torque characteristics of the inflatable robotic arms were investigated. In order to perform accurate motion control, a visual feedback control method was introduced for inflatable robotic arms. The mechanism and control system used in this paper can improve the positioning accuracy performance of inflatable robots. A 2-DOF inflatable robotic arm and a camera system were found to be able to achieve a high positioning accuracy (i.e. less than 1 mm). Abstract :